Teaching practice in elementary School in Mexico from the Pedagogy of alterity - Osuna-Lever, Cecilia (2024)
Educating in contexts of vulnerability and social impact, as is the case in Mexico, has led to seeking other ways to approach students in order to improve interpersonal relationships in the classroom. The pedagogy of alterity recognizes the individuality of the students and seeks to address their needs from an ethical and anthropological perspective. The teaching qualities highlighted by this proposal, as categories, are responsibility, protection, hope, testimony and compassion towards the other (the student). In this qualitative research designed as a biographical case study, 11 teachers who work in the Mexican educational system at the elementary level were interviewed, with the aim of identifying elements of the Pedagogy of alterity in their teaching practice. The interviews were analyzed by hand using the content aanalysis technique. The results showed the presence in the discourse of all the categories of the Pedagogy of alterity, with responsibility, acceptance and hope standing out at a higher level of importance. Likewise, intentions and actions focused on strengthening the relationship between teachers and students in their social, personal and academic context were reflected in the units of analysis. It is concluded that the practice of the Pedagogy of alterity could be an alternative that positively impacts the reduction of relational problems in the classroom.